2021
DOI: 10.3390/molecules26185529
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Unraveling the Apoptotic Potential of Rutin (Bioflavonoid) via Targeting Jab1 in Cervical Cancer Cells

Abstract: Rutin has been well recognized for possessing numerous pharmacological and biological activities in several human cancer cells. This research has addressed the inhibitory potential of rutin against the Jab1 oncogene in SiHa cancer cells, which is known to inactivate various tumor suppressor proteins including p53 and p27. Further, the inhibitory efficacy of rutin via Jab1 expression modulation in cervical cancer has not been yet elucidated. Hence, we hypothesized that rutin could exhibit strong inhibitory effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Studies conducted by other investigators revealed that rutin lowers the expression of Hes-1 and Notch-1 genes in cervical cancer cells [ 18 ]. Furthermore, rutin also induced apoptosis of cervical cancer cells by interacting with Jab1 [ 17 ]. It has been reported that notch signaling is involved in the regulation of cell-to-cell connection and cell motility which are important for the EMT of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted by other investigators revealed that rutin lowers the expression of Hes-1 and Notch-1 genes in cervical cancer cells [ 18 ]. Furthermore, rutin also induced apoptosis of cervical cancer cells by interacting with Jab1 [ 17 ]. It has been reported that notch signaling is involved in the regulation of cell-to-cell connection and cell motility which are important for the EMT of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Rutin has recently been demonstrated to regulate Notch-1 and Hes-1 mRNA levels in cervical cancer cells. Furthermore, rutin has been demonstrated to have modulated the signaling pathways in cancer cells and cause apoptosis [ 16 , 17 ]. In a recently published study, rutin was found to cause apoptosis of cervical cancer cells by downregulation of the Notch-1 and Hes-1 genes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activities of six pyrazole-based Schiff bases, 5a, 5d, 5e, 5f, 7a, and 7f, against caspase-3 and Bcl-2 were evaluated according to the reported techniques in the literature [87,88].…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Since Jab1 is an EGFR signaling target in both ER-cell lines and breast tumors, it may serve as a common factor and possible therapeutic target for crucial cell signaling pathways in ER breast cancer [21][22][23] . Elucidation of new medicinal phytochemicals targeting Jab1 signalosome provides a new path toward finding a better cancer therapeutic approach [24][25][26][27][28][29] . Jab1 has also been involved in breast cancer progression.…”
Section: Introductionmentioning
confidence: 99%